Effect of AST-120 on Endothelial Dysfunction in Adenine-Induced Uremic Rats. (14th April 2014) - Inami, Yuko; Hamada, Chieko; Seto, Takuya; Hotta, Yoko; Aruga, Seiki; Inuma, Jiro; Azuma, Kosuke; Io, Hiroaki; Kaneko, Kayo; Watada, Hirotaka; Tomino, Yasuhiko
Abstract : Aim. Chronic kidney disease (CKD) represents endothelial dysfunction. Monocyte adhesion is recognized as the initial step of arteriosclerosis. Indoxyl sulfate (IS) is considered to be a risk factor for arteriosclerosis in CKD. Oral adsorbent AST-120 retards deterioration of renal function, reducing accumulation of IS. In the present study, we determined the monocyte adhesion in the adenine-induced uremic rats in vivo and effects of AST-120 on the adhesion molecules. Methods . Twenty-four rats were divided into control, control+AST-120, adenine, and adenine+AST-120 groups. The number of monocytes adherent to the endothelium of thoracic aorta by imaging the entire endothelial surface and the mRNA expressions of adhesion and atherosclerosis-related molecules were examined on day 49. The mRNA expressions of ICAM-1 and VCAM-1 in human umbilical vein endothelial cells were also examined. Results . Adenine increased the number of adherent monocytes, and AST-120 suppressed the increase. The monocyte adhesion was related to serum creatinine and IS in sera. Overexpression of VCAM-1 and TGF- β 1 mRNA in the arterial walls was observed in uremic rats. IS induced increase of the ICAM-1 and VCAM-1 mRNA expressions in vitro . Conclusion . It appears that uremic condition introduces the monocyte adhesion to arterial wall and AST-120 might inhibit increasing of the monocyte adherence with CKD progression.